Effectiveness of Fluorescent Viability Assays in Studies of Arctic Cold Seep Foraminifera - Melaniuk, Katarzyna (Frontiers in Marine Science, 2021)
The stable isotopic signature in calcareous foraminiferal tests (CaCO3) is influenced by isotopic composition of the seawater at the time of calcification. It has been proposed that a highly negative carbon signature (δ13C) in fossil foraminifera from methane cold seeps can reflect episodes of methane release from gas hydrate dissociation or free gas reservoirs triggered by climatic changes in the past. It remains unclear if and to what extent live foraminifera incorporate methane-derived carbon during biomineralization, or whether the isotopic signature is mostly affected by authigenic overgrowth. Most studies on live foraminifera are based on the presence of Rose Bengal staining. The limitation of this method is that the cytoplasm of both live and recently dead individuals is colored, and no distinction between them can be made. In this paper, I present modern foraminiferal assemblages from a gas hydrate province Vestnesa Ridge (~1200-m, northeastern Fram Strait) and from Storfjordrenna (~400-m depth in the western Barents Sea). By using fluorescent viability assays the CellTracker™ Green CMFDA and the CellHunt Green together with conventional Rose Bengal, I was able to examine live and recently dead foraminifera separately. I show that metabolically active foraminifera inhabit methane enriched sediments at both investigated locations. Foraminiferal faunas were dominated by common Arctic species such as Melonis barleeanus, Cassidulina neoteretis, and Nonionellina labradorica. The combined usage of fluorescence probe and Rose Bengal revealed minor shifts in species compositions and differences in ratios between live and recently dead foraminifera from Storfjordrenna. There was no clear evidence that methane significantly affected the δ13C signature of the calcite of living specimens.